Houses That Remember: Readings of The Troubles in Edna O’Brien’s Fiction - Floquet, Daniel (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
This essay examines how the Irish writer Edna O'Brien represents the Irish conflict known as The Troubles in her fiction, specifically in the novelThe House of Splendid Isolation (1994) and in the short story "Black Flower", published in the collection Saints and Sinners (2011). By choosing this topic, I wish to understand if this theme represents a departure of her early narratives, as stated by some of her critics,or if it can be read in the general framework of her oeuvre.